A numerical examination of an unsteady nonlinear MHD flow in the presence of thermal radiation and heat generation - Agbaje, Titilayo; Leach, P.G.L. (Zielona Góra: Uniwersytet Zielonogórski)
In this study, the spectral perturbation method and the spectral relaxation method are used to solve the nonlinear differential equations of an unsteady nonlinear MHD flow in the presence of thermal radiation and heat generation. The SPM is mainly based on series expansion, generating series approximation coupled with the Chebyshev spectral method. The numerical results generated using the spectral perturbation method were compared with those found in the literature, and the two results were in good agreement.
Keywords: unsteady MHD flow; spectral perturbation method; spectral relaxation method; thermal radiation; heat generation